PEMAKNAAN BRAND CHINA (Studi Fenomenologi Pada Millennial Pengguna Mobil Wuling di Surabaya) - Yuniar, Alda Mega (Universitas Negeri Surabaya, 2022)
This study examines how the meaning of informants regarding a brand originating from a particular country. The purpose of this study was to find out and describe the behavior or phenomena that exist in society, especially Surabaya residents about the millennial's perception or view of a new automotive brand from China named Wuling in Indonesia. The background of this research is the rise of Wuling car users in the city of Surabaya, considering stereotype of China's image on negative aspect of product quality. Therefore, the researcher wants to know the background of users who consume Wuling brand and how they perceive Wuling brand and the current state of China. This study uses a qualitative method with a phenomenological approach. Data collection techniques with interviews, participant observation, and literature study. The results obtained from interview process of informants indicate that negative stereotypes about China, which is famous for its counterfeit products with low prices and quality, have begun to erode over time and China's efforts to improve it, one of which is by presenting Wuling products so that consumers have perspectives and meanings. positive towards Wuling and China. Keywords: Brand Image, Country of Origin, Consumer Behavior